1945
DOI: 10.1021/i560143a011
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Nitrogen in Pyridine Ring-Type Compounds by Kjeldahl Method

Abstract: THIS laboratory nitrogen must be determined by the Kjeldahl method on many types of research samples. The necessary modifications of methods for determining nitro, nitrate, azo, and other nitrogen groups are well known and reasonably

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1948
1948
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Fish (18) reduced hydrazones, semicarbazones, and similar compounds by use of zinc dust and methanol in hydrochloric acid. It has been claimed (63) that by the use of mercury or mercury-selenium oxychloride catalysts, and prolonged digestion, refractory compounds such as pyridine, quinoline, and nicotinic acid can be determined. This procedure has been adapted to micro and semimicrodeterminations (45).…”
Section: Application To More Complicated Forms Of Nitrogenmentioning
confidence: 99%
“…Fish (18) reduced hydrazones, semicarbazones, and similar compounds by use of zinc dust and methanol in hydrochloric acid. It has been claimed (63) that by the use of mercury or mercury-selenium oxychloride catalysts, and prolonged digestion, refractory compounds such as pyridine, quinoline, and nicotinic acid can be determined. This procedure has been adapted to micro and semimicrodeterminations (45).…”
Section: Application To More Complicated Forms Of Nitrogenmentioning
confidence: 99%
“…Kaye and Weiner (1945) showed that with HgO alone complete recovery of N was attained in resistant N ring compounds such as pyridine, pyrimidine, thiazole, pyrrole, quinoline and others, and White and Secor (1946) similarly showed for tryptophane and gramirddin that 60-90 minute digestion with a 5:1 ratio of HgO to compound was sufficient. Shirley and Becker (1945) found that Hg + SeOClo catalyst completely converts N in nicotine, caffeine, pyridine, and quinoline into ammonia N in three hours after "clearing'' (see also Clark, 1941). It is probable, therefore, that the combination of mercury-selenium will be more efficient as a catalyst for biological material such as seeds, than either HgO or SeO2 alone.…”
Section: Chemical Methodsmentioning
confidence: 99%
“…is obtained when a combination of selenium and mercuric oxide is,used as catalyst; this is due to the THE catalytic effect of small amounts of selenium, selenium oxychloride, selinites, or selenates in the oxidative digestion of nitrogenous organic matter by the Kjeldahl method is well known (5,13,17,20,28,32). A combination of mercuric oxide and selenium acts much more effectively than either of them singly in accelerating the decomposition of proteins (1,4, #3, 25, S3, So).…”
mentioning
confidence: 99%
“…On the other hand, provided an adequate period of afterboil following clearance of the digest is given, correct results are obtained (2, 6, 10, 26) and the erratic results sometimes obtained with selenium compounds may frequently be due to insufficient digestion (3,25,28). Clark (11) was of the opinion that many compounds, although requiring a very long digestion period, will nevertheless yield their nitrogen quantitatively to one or the other of the modified Kjeldahl procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation